AMINO ACID PROFILE OF A BASIDIOMYCETOUS EDIBLE MUSHROOM-LENTINUS SAJOR-CAJU - Lata; Atri, Narender Singh (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: In this paper amino acid profile of Lentinus sajor-caju (Fr.) Fr., a basidiomycetous mushroom has been investigated. Methods: During the evaluation 15 amino acids (lysine, aspartic acid, serine, threonine, glutamic acid, cysteine, glycine, alanine, valine, methionine, isoleucine, leucine, tyrosine, phenylalanine and histidine) were determined from the dried sample of Lentinus sajor-caju by following the standard technique of biochemistry using ion-exchange chromatography. Results: The total amino acid content has been evaluated at 18.82 g/100g. Amongst the evaluated amino acids, exogenous amino acid lysine (6.66 g/100g) is preponderantly present in comparison to all other amino acids. The essential amino acid (EAA) index (44.64%) and biological value (BV=36.93%) has also been determined for the examined sample. Conclusion: Lentinus sajor-caju (Fr.) Fr. is a potential source of quality protein with a substantial proportion of exogenous and endogenous amino acids.